Supplement to: The Importance of Choice Disability and Structural Intervention in the HIV Epidemic in Sub-Saharan Africa - de Boer, Rebecca; Musgrave, Jeffrey; Andersson, Neil; Lutscher, Frithjof (Université d'Ottawa | University of Ottawa, 2017)
Here are the Matlab files, programs and data, used to create Figures 2 and 4 in the paper: de Boer et al. (2017) The Importance of Choice Disability and Structural Intervention in the HIV Epidemic in Sub-Saharan Africa. PLoS ONE.